Rac1 is necessary for capacitation and acrosome reaction in guinea pig spermatozoa. Issue 4 (6th November 2019) - Ramírez‐Ramírez, Danelia; Salgado‐Lucio, Monica L.; Roa‐Espitia, Ana L.; Fierro, Reyna; González‐Márquez, Humberto; Cordero‐Martínez, Joaquín; Hernández‐González, Enrique O.
Abstract: Actin cytoskeleton remodeling is a critical process for the acquisition of fertilizing capacity by spermatozoa during capacitation. However, the molecular mechanism that regulates this process has not been fully elucidated. In somatic cells, Ras‐related C3 botulinum toxin substrate 1 protein (Rac1) promotes the polymerization of actin by participating in the modeling of two structures: lamellipodia and adhesion complexes linked with the plasma membrane. Rac1 is expressed in mammalian spermatozoa; however, the role of Rac1 in sperm physiology is unknown. This study aimed to elucidate the participation of Rac1 in capacitation and acrosome reaction (AR). Rac1 was found to be dispersed throughout the acrosome and without changes in the middle piece. After 60 minutes of capacitation, Rac1 was found in the apical region of the acrosome only, which concurred with an increase in Rac1‐GTP. Rac1 inhibition prevented such changes. In the middle piece, Rac1 localization remained unchanged. Besides, Rac1 inhibition blocked capacitation and AR. The present study demonstrates that Rac1 participates only in the actin cytoskeleton remodeling that occurs in the acrosomal apical region during capacitation, a region where a large amount of actin is polymerized and shaped in a diadem‐like structure. Our data also show that this actin cytoskeleton organized by Rac1 interacts with filamin‐1, and such interaction was blocked by the inhibition of Rac1, which led to a different organization of the actin cytoskeleton. All these outcomes imply that the formation of an F‐actin cytoskeleton in the acrosomal apical region is a necessary event for capacitation and AR, and which is Rac1 driven. Abstract : Ras‐related C3 botulinum toxin substrate 1 protein (Rac1) is concentrated during capacitation in the apical region of the acrosome, and its inhibition prevents the normal course of capacitation and acrosome reaction, but not the actin polymerization that occurs in the flagellum and head during capacitation. The activity of RhoA depends on the activity of Rac1, in such a way that the inhibition of Rac1 leads to an increase in the activity of RhoA, possibly RhoA is responsible for the actin polymerization in the flagellum and head. Rac1 organizes an actin cytoskeleton in the apical region of the acrosome, stabilizing the domain by anchoring certain transmembrane proteins, such as integrins.